The Origin and Construction of Pre-Hispanic Mounds in the Upper Delta of the Paraná River (Argentina) - Castiñeira Latorre, Carola (2013)
Pre-Hispanic mounds, known as ?cerritos,? ?cerri-tos de indios,? or ?aterros? across southeastern South Amer-ica, are one of the most conspicuous and well-studied culturalmanifestations in lowlands archaeology. Nevertheless, in theUpper Delta of the Paraná River, mounds are rarely studied,and even their anthropic origin is under debate. This could berelated to the fact that anthropogenic mounds are located on a floodplain where other ?mound-like? natural geoforms(generated by fluvial processes) are also present. In additionto this, the natural geoforms also contain evidence of Holo-cene human occupation (sherds, bones, charcoal, humans burials, etc.), which can lead to interpretive errors of their origin and formation. Thus, this project set out to determinethe genesis and evolution of these moundsand also toidentifythe cultural occupation and transformation of natural land-forms found in the area. In this article, natural and anthropo-genic systems and processes wereidentifiedand characterizedthrough the application of proxy record analysis (i.e., sedi-ment composition, stratigraphy, micromorphology, silica bod-ies and chronological analysis) at the Los Tres Cerros archaeological locality in the Upper Delta of the Paraná River of Victoria County, Entre Ríos Province, Argentina. This anal-ysis allowed forthe recognitionofnatural anthropogenic inter-faces, such as the ?pre-mound? occupation as well as evidenceof cultural activities such as mound construction, between1,000 and 500 14C years BP. These findings were integratedinto current research on the variability of mound constructionduring the Late Holocene in the lowlands of South America